Makna Pendidikan Multikultural dalam Perspektif Filsafat Pendidikan Islam: Studi Literatur - Andi Eki Dwi Wahyuni; Andi Marjuni; Andi Achruh (Constructivism: Journal of Research in Education, 2024)
Multicultural education plays an important role in managing the diversity of culture, ethnicity, and religion in pluralistic societies such as Indonesia. However, in practice, religious education is often taught from an exclusive perspective that may overlook the importance of appreciating diversity. Therefore, this study aims to explore the meaning of multicultural education within the framework of Islamic educational philosophy. This research employs a qualitative approach using a library research method. Data were collected from primary and secondary sources, including books, scientific journals, and other academic documents related to multicultural education and Islamic educational philosophy. The data were analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that multicultural education in the perspective of Islamic educational philosophy emphasizes values such as tolerance, equality, justice, mutual respect, and peaceful coexistence. These values are rooted in the teachings of the Qur'an and Hadith, which encourage humans to live harmoniously in diversity. Furthermore, multicultural education in Islamic education aims to develop individuals who are not only religious but also open-minded, inclusive, and capable of interacting constructively within a pluralistic society. The integration of multicultural values into Islamic education is expected to strengthen social harmony and prevent potential conflicts arising from cultural and religious differences.